Clinical usefulness of very high serum soluble interleukin-2 receptor levels for the detection of tuberculous peritonitis in a patient with chronic myelogenous leukemia. Issue 10 (October 2020) - Moriguchi, Makoto; Koh, Hideo; Hayashi, Tetsuya; Okamura, Hiroshi; Nanno, Satoru; Nakashima, Yasuhiro; Nakane, Takahiko; Imoto, Waki; Yamada, Koichi; Kakeya, Hiroshi; Hino, Masayuki; Nakamae, Hirohisa
Abstract: Tuberculous peritonitis is difficult to diagnose due to the disadvantages of ascitic culture and peritoneal biopsy. Although previous reports suggested that very high serum soluble interleukin-2 receptor (sIL-2R) levels may reflect the clinical activity of tuberculosis, little is known about the diagnostic utility of serum sIL-2R for tuberculous peritonitis. We describe a case of tuberculous peritonitis with chronic myelogenous leukemia. The abnormally high serum sIL-2R value and negative findings for other possible causes including lymphoma suggested tuberculous peritonitis and we administered anti-tuberculosis treatment before definitive diagnosis. Abnormally high serum sIL-2R levels may contribute to earlier diagnosis of tuberculous peritonitis, along with ruling out other potential differential diagnoses.